1995
DOI: 10.1051/rnd:19950510
|View full text |Cite
|
Sign up to set email alerts
|

Diet and growth during the weaning period in 3 communities in developing countries

Abstract: The aim of this study was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…1. Similar to previous reports [20,21], the present study also showed that CR mice maintain a significantly higher percentage of CD4 + and CD8 + splenocytes (15 and 35% respectively), compared to AL mice. Further, CR also significantly decreased CD19 + splenocytes (22%).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1. Similar to previous reports [20,21], the present study also showed that CR mice maintain a significantly higher percentage of CD4 + and CD8 + splenocytes (15 and 35% respectively), compared to AL mice. Further, CR also significantly decreased CD19 + splenocytes (22%).…”
Section: Resultssupporting
confidence: 92%
“…Fas‐ligand (Fas‐L), expressed predominantly on activated T lymphocytes [18], mediates cell death by cross‐linking to the Fas receptor [18,19]. Earlier studies, including our own, showed that CR modulates lymphocyte subsets and increases apoptosis [20,21]. Involvement of Fas and Fas‐L in both peripheral lymphoid cell death and lymphoid organ development is well‐established [22].…”
Section: Introductionmentioning
confidence: 98%